2004
DOI: 10.1177/0093650204267934
|View full text |Cite
|
Sign up to set email alerts
|

The Third-Person Effect and its Influence on Behavioral Outcomes in a Product Advertising Context:

Abstract: This study explored the third-person effect in the context of direct-to-consumer (DTC) advertising. A survey of 264 adults examined perceptions of DTC ad effects and their relationship to support for DTC ad regulation. Results support the third-person-effect perceptual component. The study revealed that for DTC advertising, the third-person effect operates in a multidimensional fashion through four factors (Negative DTC Ad Effects, Learning and Involvement, Patient/Provider Interaction, and Distrust of DTC Ad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 66 publications
3
67
1
2
Order By: Relevance
“…For example, one study found that participants thought that casino and lottery advertising had greater impact on other people than on themselves (Youn et al, 2000). Such systematic and self-serving differences in perceptions of the self and others are often referred to as third-person effect (Huh, Delorme, & Reid, 2004). In connection with mass media, this effect may be more pronounced if the audience regards being persuaded by the message as a sign of weakness or lack of intelligence, or if the communicator has an explicit persuasive intention or is perceived to be untrustworthy (Gunther, 1991;Youn et al, 2000).…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%
“…For example, one study found that participants thought that casino and lottery advertising had greater impact on other people than on themselves (Youn et al, 2000). Such systematic and self-serving differences in perceptions of the self and others are often referred to as third-person effect (Huh, Delorme, & Reid, 2004). In connection with mass media, this effect may be more pronounced if the audience regards being persuaded by the message as a sign of weakness or lack of intelligence, or if the communicator has an explicit persuasive intention or is perceived to be untrustworthy (Gunther, 1991;Youn et al, 2000).…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%
“…However, the influence on the distant other is perceived to be comparatively less and this could be attributed to the social distance between the self and distant others or the level of message desirability. Thus, it could be understood that the BN party supporters are persuaded by the positive and credible message given by the BN political communication devices and subsequently the voters feel "I am smart enough to recognize the value of the message" (Huh et al, 2004). Therefore, the first person or BN respondents feel proud and contented when exposed to their party communication devices and they felt that the others and distant others should also share a similar sentiment.…”
Section: Discussion On the Findings Of The Studymentioning
confidence: 99%
“…The high influence percentage on the BN party supporters triggers the possibility for a 'reverse' third-person org/10.15206/ajpor.2014.1.4.307 or first-person effect. This may be due to the perceived desirability of the BN message content to be credible or positive and thus people attribute more effects to self (Huh, Delorme, & Reid, 2004). …”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Those are factors that previous studies controlled when examining consumers' opinion of ad utility or attitudes toward DTC ads (see Moorman & Matulich, 1993;Huh, Delorme, & Reid, 2004;Perri & Nelson, 1987). Because we used self-reported measures for health literacy and educational values of DTC ads, controlling for factors that could affect respondents' attitudes toward prescription drugs was necessary.…”
Section: Methodsmentioning
confidence: 99%